Nagy nap - Sebo, Gabor (Hungary : Sebo, Gabor, 2008)
A surreal anti-euthanasia film in which three mentally disabled friends get together in one of their apartments to change their lives and become 'normal'. Soon, however, they start missing their old life even though they were labeled as idiots and come up with a rather extreme way to regain their old identities. A film about change and the potential harm it can cause.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Fiction films